Electrical spectroscopic analysis of a sheep’s kidney at low-frequencies - Faezeh Azimi Pirsoltan; Mohammad Reza Karafi (Discover Applied Sciences)
Abstract Bioelectrical Impedance Analysis (BIA) and Bioimpedance Spectroscopy (BIS) are valuable tools for characterizing tissue structure and composition. This study investigates the low-frequency electrical properties (< 10 Hz) of sheep kidney tissue using a custom-designed impedance spectroscopy system. Sheep kidneys are selected due to their anatomical and physiological similarity to human kidneys, making them a suitable ex vivo model for biomedical studies. Four kidney samples were analyzed to assess key electrical parameters, including admittance, conductivity, relative permittivity, and power factor. The results revealed a distinct peak in the imaginary part of conductivity and the admittance phase at frequencies below 30 mHz, indicating dominant capacitive behavior and energy storage mechanisms. These findings offer insights into tissue-specific dielectric responses and may support future applications in non-invasive diagnostics and therapeutic monitoring.